Anticipatory Avoidance of Contract: CISG and Egyptian Law Compared - Amin Dawwas (Nordic Journal of Commercial Law, 2012)
The United Nations Convention on Contracts for the International Sale of Goods (the Convention or CISG) was signed in Vienna in 1980 and became effective on January 1, 1988. CISG applies to contracts for the international sale of goods, i.e. contracts concluded between parties whose places of business or habitual residences are in two different states. The Convention aims at promoting international commerce by removing legal barriers in sale of goods transactions between international traders. To date, 77 States have adopted the CISG.1 This Convention entered into force in Egypt on January 1, 1988. Contracts for the sale of goods are also regulated by Egyptian law. There are two kinds of such contracts under the present Egyptian law, civil (non-commercial) and commercial contracts. The former Egyptian Commercial Code for the year 1883 had no provision relating to the sale of goods contract. Therefore, the Egyptian Civil Code governed both non-commercial and commercial sale of goods contracts. The new Egyptian Commercial Code (ECC) No. 17 for the year 1999 has reformed the field. In Articles 88-118, it governs the commercial sale contract: Articles 88-103 include general rules and Articles 104-118 govern special types of sales contracts, including the supply contract. However, ECC is not all inclusive. According to ECC Article 2, the Civil Code shall apply in absence of a commercial rule in the Commercial Code. Accordingly, the non-commercial sale of goods contract is entirely governed by the Civil Code. In addition, the commercial sale of goods contract is basically governed by the (new) Commercial Code; and, in absence of any rule in this code, resort shall be made to the Civil Code. CISG deals with anticipatory avoidance of contract. In general, if prior to the date for performance of the contract it is clear that one of the parties will commit a fundamental breach of contract, the other party may – under CISG Article 72 - declare the contract avoided. The party intending to declare the contract avoided must give reasonable notice to the other party, in order to allow him to provide adequate assurance of his performance. Nevertheless, such notice is not necessary, if time does not allow for providing it, or if the other party has declared that he will not perform his obligations. CISG also particularly governs anticipatory avoidance of installment contracts. ‘The contract calls for the delivery by instalments if it requires or authorizes the delivery of goods in separate lots’.2 CISG Article 73(2) clearly says: ‘If one party's failure to perform any of his obligations in respect of any instalment gives the other party good grounds to conclude that a fundamental breach of contract will occur with respect to future instalments, he may declare the contract avoided for the future, provided that he does so within a reasonable time.’3 In its Article 223, the Egyptian draft Civil Code explicitly regulated the anticipatory avoidance of contracts. It stated: ‘In synallagmatic contracts, if one of the parties suffers a decrease in his assets after the contract is concluded, or his creditworthiness is reduced so that there are fears that he will not be able to perform his obligation, the other party – if he has to perform first – may not perform until the first party performs what he undertook or provides adequate assurance for such performance. Where this obligation is not performed or the assurance is not provided within a reasonable time termination of the contract may be requested’.4 However, the present Egyptian Civil Code does not recognize the anticipatory avoidance doctrine.5 Generally, given the inherent uncertainty in assessing future events, it is impossible to know with certainty prior to the time of performance that the party in difficulty will commit a breach.6 As a result, the Egyptian legislator explicitly recognizes termination of contracts on the ground of actual breach only. Article 157(1) of the Egyptian Civil Code says: ‘In synallagmatic contracts, if one of the parties fails to perform his obligation, the other party may, after serving a warning upon him, request performance of the contract or its termination, with damages in either case if needed’. According to the general rules of the Civil Code, the creditor must not himself be in default and must be able to restore the status quo ante, too.7 Nevertheless, the Egyptian Civil Code includes some provisions that indirectly cover anticipatory breach of contract. Article 220 governs situations in which a party declares that he will not perform his obligation. Articles 220 and 273 deal with circumstances in which a party will not be able to perform his obligation in due date. This paper will clarify whether the aggrieved party may avoid the contract in such cases or not. The new Egyptian Commercial Code has reformed the anticipatory avoidance ("termination", in the context of ECC) of the sale of goods contract, in that it has put an end to halting future performance. Like CISG, ECC governs the contract for the sale of goods by installments. Concerning the anticipatory avoidance of installment contract, ECC Article 97 says in part: ‘If it is agreed that the thing sold shall be delivered by installments, the buyer may request termination if the seller fails to perform one of the deliveries in the time agreed upon’.8 ECC Article 117 deals, in a clearer way, with the concept of anticipatory avoidance with respect to the supply contract. It states in toto: ‘If either party fails to perform his obligations relating to one of the periodic supplies, the other party may not terminate the contract unless such failure to perform causes gross harm to him or weakens confidence in the ability of the defaulting party to continue performing subsequent supplies on a regular basis’. ECC differentiates between local and international commercial sale of goods contracts. ECC Article 88/2 subjects the international commercial sale of goods contract to international conventions effective in Egypt, i.e. CISG, and international commercial practice. The local commercial sale of goods contract is governed by the ECC rules as augmented with Civil Code rules. According to the ECC’s memorandum, CISG was one of the instruments with which ECC has been influenced.9 The aim of this paper is to see to which extent do Articles 97 & 117 ECC plainly harmonize with CISG with respect to anticipatory avoidance. All respective rules of the Egyptian Civil Code (e.g. Articles 220 & 273) will also be tackled. In accordance, this paper will examine the requirements for anticipatory avoidance in section two and all legal effects resulting from meeting such requirements under both CISG and Egyptian law, in section 3.